Lack of CD56 expression on myeloma cells is not a marker for poor prognosis in patients treated by high-dose chemotherapy and is associated with translocation t(11;14) - Hundemer, Michael; Klein, Ulrike; Hose, Dirk; Raab, Marc-Steffen; Cremer, Friedrich Walter; Jauch, Anna; Benner, Axel; Heiß, Christiane; Moos, Marion; Ho, Anthony Dick; Goldschmidt, Hartmut (Bone marrow transplantation, 2007)
Lack of CD56 expression was reported to be associated with a poor prognosis in multiple myeloma (MM) patients treated with conventional chemotherapy. Aim of our retrospective study was to analyse whether CD56 expression on MM cells reveals as a prognostic factor in patients treated with high-dose chemotherapy. MM cells of 99 patients prior to treatment with high-dose chemotherapy were analysed for CD56 expression by flow cytometry. Multivariable analysis of event-free survival in these patients showed no statistically significant difference between the CD56(-) (n=28) and the CD56(+) (n=71) group. The lack of CD56 expression on MM cells of these patients correlated significantly with the presence of translocation (11;14) (t(11;14)) (estimated correlation coefficient=0.655 95%, confidence interval (0.481; 0.779)). In summary, our results indicate that lack of CD56 expression on MM cells is not a prognostic marker in patients treated with high-dose chemotherapy, but is associated with t(11;14).
Gesehen am 20.10.2021